The religions of the book: Christian perceptions, 1400 - 1660 - Dimmock, Matthew (Early modern literature in history, 2008)
Introduction: the devil citing scipture: Christian perceptions of the religions of the book / Matthew Dimmock and Andrew Hadfield -- Christian antisemitism and intermedial experience in late medieval England / Anthony Bale -- The Crusade of Varna, 1443-1445: what motivated the crusaders? / Colin Imber -- "A human head to the neck of a horse": hybridity, monstrosity and early Christian conceptions of Muhammad and Islam / Matthew Dimmock -- "Vile interpretations" and "devilish supplements": Jewish exegesis and linguistic siege in Martin Luther's On the Jews and their lies (1543) / Raphael Hallett -- "Turks" and "Christians": the iconography of possession in the depiction of the Ottoman-Venetian-Hapsburg frontiers, 1550-1689 / Palmira Brummett -- Confounding Babel: the language of religion in the English Revolution / Matthew Birchwood -- "A parallel made with the Jewish sanhedrin": tolerating Jews and Jewish precedents in the early modern church and state / Eliane Glaser -- Milton among the Muslims / Gerald MacLean